DIABETIC KETOACIDOSIS IN CHILDREN AND ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS AND ASSOCIATED RISK FACTORS - Ramos, Thaynara Tavares Oliveira; Noronha, Juliana Andreia Fernandes; Lins, Brenda Sales; Santos, Maria Cecília Queiroga dos; Santos, Sheila Milena Pessoa dos; Cantalice, Anajás da Silva Cardoso (Cogitare Enfermagem, 2022)
Objective: to estimate the prevalence and risk factors of diabetic ketoacidosis in children and adolescents with Type 1 Diabetes Mellitus. Method: an epidemiological, cross-sectional and cohort study that analyzed the medical charts of children and adolescents with Type 1 Diabetes Mellitus admitted over a 10-year period to a public reference hospital in the municipality of Campina Grande, Brazil, from 2009 to 2019. The data were analyzed by means of descriptive statistics, both bivariate and multivariate through Poisson regression. Results: 130 medical charts were analyzed, of which 46.2% presented diabetic ketoacidosis. The independent variables that significantly and jointly impacted on the outcome were the following: age, infection, diet error and error in insulin dosage. Conclusion: diabetic ketoacidosis was a common finding in children and adolescents with Type 1 Diabetes Mellitus. The results contribute to Nursing care and allow implementing intervention for the prevention and adequate management of the problem.